The teacher's role in developing learner autonomy - Yelshina, М.К. (Karagandy University of the name of acad. E.A. Buketov, 2023)
The author of the article analyzes the concept of "learning autonomy" based on the works of foreign experts, provides different views on the interpretation of this concept. The article discusses the role and functions of the teacher in the development of learner autonomy. The components of learning autonomy are also described.
Keywords: learning autonomy; learner autonomy; self-education; self-organization